Proceedings of the 21st International Conference on Distributed Computing and Networking 2020
DOI: 10.1145/3369740.3369796
|View full text |Cite
|
Sign up to set email alerts
|

DroidLight

Abstract: Smartphone malware attacks are increasing alongside the growth of smartphone applications in the market. Researchers have proposed techniques to detect malware attacks using various approaches, which broadly include signature and anomaly-based intrusion detection systems (IDSs). Anomaly-based IDSs usually require training machine learning models with datasets collected from running both benign and malware applications. This may result in low detection accuracy when detecting zero-day malwares, i.e. those not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Depending on how serious the anomaly is and how the system is set up, automated actions like app quarantine, user notification etc. may be started [15]. [14] observed that detecting mobile malware has become essential as popular platforms such as Android and iOS face growing vulnerabilities, resulting in a billion-dollar industry that exploits victims for revenue.…”
Section: Anomaly Based Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on how serious the anomaly is and how the system is set up, automated actions like app quarantine, user notification etc. may be started [15]. [14] observed that detecting mobile malware has become essential as popular platforms such as Android and iOS face growing vulnerabilities, resulting in a billion-dollar industry that exploits victims for revenue.…”
Section: Anomaly Based Detectionmentioning
confidence: 99%
“…They suggests avenues for further studies to enhance detection accuracy, scalability, evasion resilience against attacks in malware detectors discussing important issues that should be considered when investigating emerging technology trends while addressing present limitations facing this field. Sakil Barbhuiya et al ( 2020) [15] focuses on the Smartphone Intrusion Detection Systems (IDSs) are categorized into categories: efficient IDSs and one-magnificence type for phone IDSs. Efficient IDSs encompass signature-based totally and anomaly-based totally systems.…”
Section: Anomaly Based Detectionmentioning
confidence: 99%
“…Even though ML algorithms have not always been successful in detecting zero-day attacks, the recent studies seem to challenge this. In [151], the authors presented a solution based on a refined one class classification (OCC) models which were selected based on the application running in the foreground. Using the scenarios of information theft, currency-mining bot, and DDoS attack on a smartphone, the authors showed that their method was able to detect zero-day malware effectively, without significant overhead.…”
Section: B Researching New Features For Shallow Machine Learningmentioning
confidence: 99%